Pengaruh Kemampuan Manajerial Terhadap Kinerja Pejabat Dinas Pendidikan Se Sumatera Selatan - Arwan Arwan (El-Idare, 2022)
This study aims to determine the extent of the influence of Managerial Skills on the Performance of Local Government Officials in the Education Sector in South Sumatra. The research was conducted in South Sumatra from March to May 2010. The population of this study were echelon III officials within the Education Office. Data were collected from 75 echelon III officials as a randomly selected sample and the data were analyzed by path analysis after all variables were entered into the correlation matrix. The results showed that the performance of echelon III officials was directly influenced by managerial skills. The results of this study are (1) managerial skills have a direct effect on organizational culture, and (2) managerial skills have a direct effect on performance. Therefore, in improving the performance of leaders, managerial skills must be a strategic consideration in planning at the South Sumatra Provincial Education Office; but other variables need to be taken into account by the next performance researcher.